Towards an unbiased jet energy loss measurement - Liliana Apolinário; Lénea Luís; José Guilherme Milhano; João M. Silva (Journal of High Energy Physics)
Abstract The modifications imprinted on jets due to their interaction with Quark Gluon Plasma (QGP) are assessed by comparing samples of jets produced in nucleus-nucleus collisions and proton-proton collisions. The standard procedure ignores the effect of bin migration by comparing specific observables for jet populations at the same reconstructed jet transverse momentum (p T ). Since jet p T is itself modified by interaction with QGP, all such comparisons confound QGP induced modifications with changes that are simply a consequence of comparing jets that started out differently. The quantile matching procedure introduced by Brewer et al. directly estimates average fractional jet energy loss (Q AA ) and can thus mitigate this p T migration effect. In this work, we validate the procedure in more realistic scenarios that include medium response. We study the evolution of Q AA with jet radius, its sensitivity to minimum particle p T and medium response as implemented in two different models for jet evolution in heavy-ion collisions. Further, we use this procedure to establish that the difference between inclusive jet and γ+jet nuclear modification factors (R AA ) is dominated by differences in the spectral shape, leaving the colour charge of the jet initiating parton with a lesser role to play. Additionally, we compare Q AA to an experimentally proposed proxy for fractional jet energy loss, S loss , showing that both quantities are similar, although the former provides a more clear physical interpretation. Finally, we show the size of the p T migration correction for four different substructure observables and how to reliably use the quantile procedure experimentally to improve existing measurements.